TECHNOLOGY ACCEPTANCE MODEL ON DIGITAL BANKING SERVICE LIVIN' BANK MANDIRI ON TRUST AND ITS IMPACT ON CUSTOMER LOYALTY - Ria Marlina; Jerry Heikal (Sean Institute, 2023)
This study aims to test the expected research model and be able to obtain the results of the influence of the technology acceptance model on digital banking services livin' Bank Mandiri on trust and its impact on customer loyalty. Questionnaire respondent data was obtained from Bank Mandiri customers who had used digital banking service livin' Bank Mandiri' and then distributed questionnaires online through the